How physical activity enhances academic engagement in middle school: a serial mediation model of interpersonal relationships and academic support - Zhang, Junmin; Liu, Yongfeng; Zhang, Xiaogang; Hu, Shuiyou (Frontiers in Psychology, 2025)
IntroductionAcademic engagement is a critical aspect of adolescent development. Understanding the mechanism of academic engagement will help to take effective measures to improve the academic engagement of middle school students. This study used a serial mediation model to delve into the complex association among physical activity, interpersonal relationships, academic support, and academic engagement in middle school students.MethodsA sample of 746 participants in middle school (51.1% female) completed validated measurement tools for each variable.ResultsResults showed that grade was negatively correlated with physical activity and academic engagement, yet positively associated with interpersonal relationships, and significant positive correlations among the four variables. In contrast, gender and only-child status had weak correlations with other measured variables. Findings from regression analyses further underscored that physical activity positively directly predicted academic engagement. Notably, mediation analyses showed that both interpersonal relationships and academic support mediated the separate relationship between physical activity and academic engagement, and they also supported the hypothesized serial mediation effect. The final serial mediation model effectively explained a substantial 31.8% portion of the variance in academic engagement.DiscussionThese findings comprehensively illustrate the complex interactions between physical activity and academic engagement, deepening our understanding of the determinants of the relationship between the two variables among middle school students. The study provides valuable empirical evidence for designing targeted interventions aimed at enhancing adolescents’ academic engagement through improved physical activity, interpersonal relationships, and academic support.